Формирование имиджа регионов России: проблемы и перспективы - Chizh F. V., Shapovalova O. N. (Academic community of students, 2016)
in this work, the problems of forming the image of the regions of Russia at the present stage of their development are considered.
Keywords: имидж регионов; проблематика развития имиджа; имиджевая политика; реклама городов; image of regions; problems of image development; image policy; advertising of cities